Developments in spontaneous and coherent Raman scattering microscopic imaging for biomedical applications. (26th October 2015) - Krafft, C.; Schie, I. W.; Meyer, T.; Schmitt, M.; Popp, J.
Abstract : An overview about the instrumentation for spontaneous and coherent Raman scattering microscopic imaging is given with a focus on recent developments. Abstract : First, the potential role of Raman-based techniques in biomedicine is introduced. Second, an overview about the instrumentation for spontaneous and coherent Raman scattering microscopic imaging is given with a focus of recent developments. Third, imaging strategies are summarized including sequential registration with laser scanning microscopes, line imaging and global or wide-field imaging. Finally, examples of biomedical applications are presented in the context of single cells, laser tweezers, tissue sections, biopsies and whole animals.